HAND HYGIENE AND HEALTH: AN EPIDEMIOLOGICAL STUDY OF STUDENTS IN AMRAVATI - Tambekar, Dilip H; Shirsat, S. D.; Kakade, S. R.; Ambekar, K. B. (African Journal of Infectious Diseases (AJID), 2009)
Hands may be the most important means by which enteric pathogens are transmitted. Skin hygiene particularly of the hands, has been accepted as a primary mechanism to control the spread of infectious agents. Therefore the present study was undertaken to evaluate the number and type of enteric bacterial pathogens associated with hands. A total of 160 hands swab samples of 80 students of KG, PS, SS, UG, and PG were analyzed. Pathogens were isolated from hands includes Escherichia coli (22%), Pseudomonas aeruginosa (12%), Staphylococcus aureus (15%), Proteus mirabilis (11%), Citrobacter freundii (10%), Enterobacter aerogenes (8%), Streptococcus sp. (7%), Klebsiella sp. (6%), Micrococcus sp. (5%) and Salmonella typhi (4%). The prevalence of the bacterial pathogens was high in students of K.G. and primary than those in secondary schools and colleges. The data indicated that the hands of the female were more contaminated than male and the left hand was more contaminated than the right hand. Thus, the potential risk factors for transmission of enteric pathogens through hands should be investigated in order to improve the general health of the students.